2019
DOI: 10.2147/ndt.s186892
|View full text |Cite
|
Sign up to set email alerts
|

<p>A novel approach to cardiovascular disturbances in patients with schizophrenia spectrum disorders treated with long-acting injectable medication</p>

Abstract: PurposeThis research article assesses the cardiovascular impact of long-term injectable antipsychotic therapy on patients diagnosed with schizophrenia spectrum disorders. In our study, we attempted to quantify the potential causes of cardiovascular damage, assess cardiovascular parameters, and correlate them with the time elapsed from the onset of the psychosis until the initiation of injectable antipsychotic therapy, as well as the duration of long-acting therapy, and finally, to compare two of the most utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These were represented by new, well-chosen drugs according to international recommendations (most probably as a consequence of being prescribed by specialists). 34,35 Conversely, the EPCCs collected in Arad had a lower percentage of psychotropic drugs (probably because most were penned by a GP).…”
Section: Discussionmentioning
confidence: 99%
“…These were represented by new, well-chosen drugs according to international recommendations (most probably as a consequence of being prescribed by specialists). 34,35 Conversely, the EPCCs collected in Arad had a lower percentage of psychotropic drugs (probably because most were penned by a GP).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Many studies have shown aberrant levels of a range of inflammatory markers in SZ patients. [9][10][11] Decreased levels of sICAM-1 in SZ could represent the reduced activity of the type-1 immune system, [12][13][14] but the role of inflammation and immune activation in severe mental disorders is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of the psychiatric symptoms was assessed with BPRS-E. We chose the expanded version (24 items) of BPRS because it appears to assess better affective and schizophrenic symptoms than the previous (18 items) version [ 38 , 39 , 40 ]. The cardiac EF was measured by a cardiologist using TSTE because the three-dimensional strain analysis better detects subclinical changes in the cardiac muscle [ 41 ].…”
Section: ⧉ Patients Materials and Methodsmentioning
confidence: 99%